Effectiveness of Postpartum Exercise and Music Therapy in Reducing Anxiety in Postpartum Mothers - Karnilan Lestari Ningsi Sam (Indonesian Journal of Global Health Research, 2025)
Data shows that 16.2% of mothers were diagnosed with a pure anxiety disorder (phobia, panic, acute adjustment disorder with anxiety) 6 weeks after giving birth, in addition, 82% of diagnosed phobias were first discovered during the postpartum period. Untreated anxiety can lead to depression. Objective to find out the Effectiveness of Postpartum Exercise and Music Therapy in Reducing Anxiety in Postpartum Mothers. Using the true experimental design method using one group design, pre test-post test design, sampling technique using purposive sampling with 61 research samples. Postpartum Mothers will have their Anxiety scale measured using the State Anxiety Invantory Score (STAI), data analysis is carried out univariately to describe the frequency distribution and bivariately using the Wilcoxon test. The results of the Wilcoxon signed rank test statistical test show a value of ρ < 0.001, which means that there is an effect of reducing anxiety in postpartum mothers with non-pharmacological therapy, namely postpartum gymnastics and music therapy. Postpartum Exercise and music therapy can reduce anxiety in postpartum mothers.